Molecular systematics and historical biogeography of Maianthemum s.s. Issue 6 (20th June 2017) - Kim, Changkyun; Cameron, Kenneth M.; Kim, Joo‐Hwan
Abstract : PREMISE OF THE STUDY: Understanding the underlying mechanisms for the evolution of intercontinental disjunct patterns has long fascinated botanists. We present a molecular phylogenetic reconstruction of Maianthemum s.l. (including Smilacina ) with a focus on Maianthemum s.s. species, which have a disjunct distribution between Eurasia and North America. Within this evolutionary framework, we clarify the systematic classification and biogeographical history of Maianthemum s.s. METHOD: Data from two nuclear and five chloroplast DNA regions were analyzed using the programs PAUP*, RAxML, MrBayes, BEAST, and RASP. KEY RESULTS: Our molecular phylogeny supports Maianthemum s.s. as monophyletic. Maianthemum bifolium and M. canadense are grouped according to their taxonomic species, but the accessions of M. dilatatum are divided into two well‐defined groups, i.e., one comprising western North American accessions, and the other composed of northeast Asian accessions. Molecular dating and biogeographic reconstructions suggest a northeast Asian origin for Maianthemum s.s. and that a complicated pattern of divergent evolution began approximately in the late Miocene. Intercontinental disjunctions of Maianthemum s.s. in the Northern Hemisphere appear to have occurred two times during the Pliocene. CONCLUSIONS: Based on our results, two possible ways to treat Maianthemum s.s. species can be envisioned: (1) elevate Asian populations of M. dilatatum to specific rank; or (2) combine the three Maianthemum s.s. species into a broadly defined single species. We recommend treatment of Maianthemum s.s. as a single species. The biogeographic patterns of Maianthemum s.s. coupled with molecular dating suggest both vicariance and long‐distance dispersal events as key mechanisms for diversification of the clade.